A quality in education of lower central network school with coaching and mentoring pass online system (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A quality in education of lower central network with coaching and mentoring pass online system consisting of teachers,administrators by using the concept and activities of the mentoring system. The purposes were as 1) To Assess the promotion ofknowledge and understanding of concepts used in the development of production and teacher development systems in relevanttarget groups consisting of teachers, administrators using concepts and activities, mentoring systems, Coaching and Mentoringand 2) To develop the system and the process of teaching and learning management by having teachers remove the knowledgemanagement (KM) in classroom by developing a mentor for the target group with participating in the phase 1 project will applythe knowledge in real situations in the lower central region network schools and building a professional community of learning(Professional Learning Community: PLC) by the university professors do research to develop teaching and learning and developteachers in small schools as well as "coaches" for teachers to use innovations developed for their students in this research usingquantitative research methods and integrated experiments (Quantitative-Experiment Research) The researcher has set theframework for the research guidelines. The population for this research with selected purposive sampling by considering thecontext of responsibilities with university. In the network area of the lower central region which are small and voluntary schoolsof 30 schools, 98 teachers (science and math teachers), 22 university professors (teachers responsible for monitoring all 30schools) for the academic year 2019. Data analysis using the statistics of percentage (%) average ( x ̅ ) standard Deviation (S.D.)and qualitative data analysis. The results of the research were findings: 1) Assessment in the promotion of knowledge andunderstanding of concepts used in the development of production and teacher development systems Develop relevant targetgroups consisting of teachers, administrators using concepts and activities, mentoring systems, coaching and mentoring thesatisfaction at the highest level (x ̅ =4.74, S.D.=0.37) and 2) Development a system and learning process by having the teacherto remove the knowledge management (KM) in classroom consisting of 1) Learning Management with coaching and mentoringprocess, 2) Development of competency based learning with imagination (Competency Based on Imagination), 3) Supportingthe process of building empirical knowledge (Construction of Knowledge), and 4) Performance Review for Creation ofInnovation..